Employee Satisfaction Factors in the E-Commerce Company: The Mediating Role of Employee Engagement - Ahmad Azmy (Journal of Indonesian Economy and Business, 2024)
Introduction/Main Objectives: This study discusses the factors that have implications for job satisfaction in e-commerce companies. The focus of the study is to analyze the organizational commitment, spiritual leadership, and technological advancement, which are mediated by employee engagement. Background Problems: Some e-commerce companies have problems with their employees’ level of satisfaction. This study provides recommendations for dealing with the satisfaction factors of employees working in e-commerce. Novelty: The novelty of this study is that it offers a different model for measuring job satisfaction. Employee engagement is used as a mediating variable to measure the implications for employee satisfaction in e-commerce companies. One of the variables used is technological advancement. Research Methods: This study uses the PLS-SEM method. The total respondents is 250 employees who work in e-commerce companies. Purposive sampling is used, according to the research needs, with a total of 207 respondents. The object of this study is a business organization that is engaged in e-commerce. Finding/Results: The direct and indirect effects of employee satisfaction are implied by spiritual leadership and organizational commitment. Technological advancement has no direct or indirect effect on employee satisfaction. Employee engagement has a mediating role in both the direct and indirect effects on employee satisfaction. Conclusion: E-commerce organizations should pay more attention to their employees’ development through building their technological capabilities. This research can explain the improvement in a business’s quality through its employees’ satisfaction. This adds value to human resources management.